2019
DOI: 10.20979/ueyd.617746
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Doğrudan Yabancı Yatırımlar, Karbon Emisyonu ve İktisadi Büyüme: Veriye Dayalı Bir Analiz

Abstract: Böylece çalışmada, değişkenler arasındaki dolaylı ve dolaysız nedenselliklerin ve doğrudan yabancı yatırımların çevresel etkilerinin ortaya konulması amaçlanmıştır. Elde edilen DAGs şablonları, doğrudan yabancı yatırımların dolaylı olarak dış ticaret üzerinden karbon emisyonlarını tetiklediğini, karbon emisyonları ve enerji tüketiminin ise ekonomik büyümeyi takip ettiğini ortaya koymaktadır. DAG şablonları ayrıca, kirliliğin, enerji tüketiminin doğrudan bir belirleyicisi olduğunu göstermektedir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
0
2
0
3
Order By: Relevance
“…However, it is positive for Serbia, Ukraine, and Russia. Benli (2020) examines the connection among foreign direct investment (FDI), CO 2 , enco, EG, and some other economic variables in Turkey. Results reveal that FDI indirectly triggered CO 2 via foreign trade, while CO 2 and enco follow EG.…”
Section: III Studies On Findev Eg Enco and Co 2 Emissionsmentioning
confidence: 99%
“…However, it is positive for Serbia, Ukraine, and Russia. Benli (2020) examines the connection among foreign direct investment (FDI), CO 2 , enco, EG, and some other economic variables in Turkey. Results reveal that FDI indirectly triggered CO 2 via foreign trade, while CO 2 and enco follow EG.…”
Section: III Studies On Findev Eg Enco and Co 2 Emissionsmentioning
confidence: 99%
“…Accordingly, it has been demonstrated that the Pollution Haven Hypothesis is valid in Turkiye. Moreover, Benli (2020) tested the relationship between CO2 emissions, FDI and many other variables, using Turkiye's 1974-2014 data and the Directed Non-Cycle Graphs (DAGs) Method, and found that FDI indirectly affects CO2 emissions through foreign trade. Omri et al (2014) examined the correlation between GDP growth, FDI, and CO2 emissions (data from 54 economies the years 1990 to 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Granger nedensellik bulguları ekonomik büyümenin enerji tüketimi ve doğrudan yabancı sermaye girişinin nedeni olduğunu göstermiştir. Benli (2020) Türkiye ekonomisi için doğrudan yabancı yatırımlar, karbon emisyonu, ekonomik büyüme ve enerji tüketimi ilişkisini incelemiş ve doğrudan yabancı yatırımların karbon emisyonlarını tetiklediği sonucuna ulaşmıştır. Jebli ve diğerleri (2020) çalışmalarında farklı gelir seviyesine sahip 102 ülkede yenilenebilir enerji tüketiminin CO2 emisyonunu azalttığını bulmuşlardır.…”
Section: Ekonomik Büyüme Yenilenebilir Enerji Tüketimi Ve Doğrudan Yabancı Sermaye Yatırımları-çevre İlişkisini İnceleyen çAlışmalarunclassified